COVID-19-Induced Thrombosis in Patients without Gastrointestinal Symptoms and Elevated Fecal Calprotectin: Hypothesis Regarding Mechanism of Intestinal Damage Associated with COVID-19 - Mauro Giuffrè; Stefano Di Bella; Gianluca Sambataro; Verena Zerbato; Marco Cavallaro; Alessandro Agostino Occhipinti; Andrea Palermo; Anna Crescenzi; Fabio Monica; Roberto Luzzati; Lory Saveria Crocè (Tropical Medicine and Infectious Disease, 2020)
Background: Patients with coronavirus infectious disease 2019 (COVID-19) and gastrointestinal symptoms showed increased values of fecal calprotectin (FC). Additionally, bowel abnormalities were a common finding during abdominal imaging of individuals with COVID-19 despite being asymptomatic. The current pilot study aims at evaluating FC concentrations in patients without gastrointestinal symptoms. Methods: we enrolled 25 consecutive inpatients with COVID-19 pneumonia, who were admitted without gastrointestinal symptoms and a previous history of inflammatory bowel disease. Results: At admission, 21 patients showed increased FC with median values of 116 (87.5; 243.5) mg/kg despite absent gastrointestinal symptoms. We found a strong positive correlation between FC and D-Dimer (r = 0.745, p < 0.0001). Two patients developed bowel perforation. Conclusion: our findings may change the current understanding of COVID-19 intestinal-related disease pathogenesis, shedding new light on the potential role of thrombosis and the consequent hypoxic intestinal damage.